2019
DOI: 10.1038/s41598-018-38032-1
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum specific helicase 2 is a dual, bipolar helicase and is crucial for parasite growth

Abstract: Human malaria infection is a major challenge across the globe and is responsible for millions of deaths annually. Rapidly emerging drug resistant strains against the new class of anti-malarial drugs are major threat to control the disease burden worldwide. Helicases are present in every organism and have important role in various nucleic acid metabolic processes. Previously we have reported the presence of three parasite specific helicases (PSH) in Plasmodium falciparum 3D7 strain. Here we present the detailed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…It can unwind DNA in both the 3′–5′ and 5′–3′ directions. Its dual and bipolar helicase activities are similar to other previously characterized helicases present in P. falciparum such as PfDH60, PfH45, and PfPSH2 . PfPSH1 shows similar activities to PfPSH2 as both are dual and bipolar helicases.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…It can unwind DNA in both the 3′–5′ and 5′–3′ directions. Its dual and bipolar helicase activities are similar to other previously characterized helicases present in P. falciparum such as PfDH60, PfH45, and PfPSH2 . PfPSH1 shows similar activities to PfPSH2 as both are dual and bipolar helicases.…”
Section: Discussionsupporting
confidence: 70%
“…The subcellular localization of PfPSH1 was studied with the help of immunofluorescence microscopy, and it is majorly present in the cytoplasm and partially in the nucleus of the parasite in all the intraerythrocytic developmental stages. It has been previously reported that PfPSH2 and PfPSH3 are localized in both nucleus and cytoplasm in intraerythrocytic developmental stages .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations